2020
DOI: 10.1055/s-0040-1701694
|View full text |Cite
|
Sign up to set email alerts
|

Changing Landscape of Dravet Syndrome Management: An Overview

Abstract: Dravet syndrome (DS), previously known as severe myoclonic epilepsy of infancy, is a severe developmental and epileptic encephalopathy caused by loss-of-function mutations in one copy of SCN1A (haploinsufficiency), located on chromosome 2q24, with decreased function of Nav1.1 sodium channels in GABAergic inhibitory interneurons. Pharmacoresistant seizures in DS start in the infancy in the form of hemiclonic febrile status epilepticus. Later, other intractable seizure types develop including myoclonic seizures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…In DS or “severe myoclonic epilepsy of infancy”, healthy children typically develop seizures between the age of five to eight months [ 7 , 62 , 63 ]. Seizures may be triggered by fever, vaccination, stress, and bathing.…”
Section: Developmental and Epileptic Encephalopathies (Dees)mentioning
confidence: 99%
See 2 more Smart Citations
“…In DS or “severe myoclonic epilepsy of infancy”, healthy children typically develop seizures between the age of five to eight months [ 7 , 62 , 63 ]. Seizures may be triggered by fever, vaccination, stress, and bathing.…”
Section: Developmental and Epileptic Encephalopathies (Dees)mentioning
confidence: 99%
“…Seizures may be triggered by fever, vaccination, stress, and bathing. Children experience prolonged hemiconvulsive or generalized febrile seizures during the first year of life [ 62 , 63 ]. This is followed by multiple types of intractable afebrile seizures, frequent occurrence of status epilepticus, and psychomotor retardation [ 63 ].…”
Section: Developmental and Epileptic Encephalopathies (Dees)mentioning
confidence: 99%
See 1 more Smart Citation
“…A highly purified form of pharmaceutical CBD has been approved for drug-resistant seizures associated with Dravet syndrome and Lennox-Gastaut syndrome [50,51]. Open-label trials of a pharmaceutical-grade CBD and other artisanal CBD products have shown long-term efficacy and safety of CBD in various other treatment-resistant epilepsy such as tuberous sclerosis, CDKL5 deficiency disorders, Aicardi syndrome, 15q duplication, and Doose syndrome.…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…The resulting excitation/inhibition imbalance leads to network hyperexcitation and epileptic seizures, as well as other manifestations of DS ( Scheffer and Nabbout, 2019 ). Small-molecule and device-based treatments for DS, approved and under clinical development, were reviewed recently ( Samanta, 2020 ). As SCN1A mutations are not known to produce toxic protein, upregulation of the remaining healthy SCN1A allele represents a desirable therapeutic target in DS.…”
Section: Nbts In Orphan Neurological Disordersmentioning
confidence: 99%